DIFUSI INOVASI APLIKASI SI D’nOK DALAM PENERBITAN DOKUMEN KEPENDUDUKAN DI KOTA SEMARANG - Praria Laharu, Rizky; Warsono, Hardi; Sunu Astuti, Retno (Journal of Public Policy and Management Review, 2024)
The SI D'nOK innovation is the only online-based innovation that helps with the issuance of population documents. The SI D'nOK innovation was created and disseminated by the Semarang City Population and Civil Registration Service. However, public knowledge of the SI D'nOK application is very lacking and the operation of the SI D'nOK application is still below standard. This is used as the background for this research. This research aims to analyze the diffusion of innovation and the obstacles that occur in the process of diffusion of innovation in the SI D'nOK application in publishing population documents in Semarang City. The research method used is descriptive qualitative using interview, observation and documentation data collection techniques. This research uses the theory of diffusion of innovation according to Everret M. Rogers, namely innovation, communication channels, time period and social system to barriers to the diffusion of innovation. The research results show that the diffusion of SI D'nOK application innovation has gone well. This is supported by community needs. The public knows the innovation of the SI D'nOK application according to interpersonal channels and mass media channels. The time period for receiving is quite long and is influenced by the presence of an authority figure. However, the lack of human resources and operators in carrying out multiple tasks causes the service to take a long time. Based on past experience, it will influence the spread of SI D'nOK application innovation.